Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Ulang Mahasiswa Membeli Smartphone Samsung Android di Universitas Negeri Padang - Liza Yuliana (Journal of Economics and Management Scienties, 2023)
This study aims to determine the effect of brand equity on purchase decisions for samusng android smartphones at Padang State University. The research was conducted at the State University of Padang, and the population in this study are all consumers who have ever purchased Samsung Android smartphone products. Sample taken by accidental sampling method. The sample size is 150 people. The technique used for data analysis is multiple regression. These results indicate that: 1) Brand Awareness has a significant effect on purchasing decisions for samsung android smartphones in the State University of Padang, 2) Perceived Quality significantly influences to the [ruling repurchase of samsung android smartphones in the State University of Padang, 3) Brand Association have a significant effect on purchase decisions reset samsung android smartphone at the State University of Padang, and 4) Brand Loyalty significantly influence the purchasing decision samsung android smartphone at PadangState University.